Respon Investor Terhadap Corporate Actions (Produk Baru & Inovasi Sistem Dan Teknologi) Pada Sektor Otomotif Di Asia Timur - Dea Devina Theja; Juniarti Juniarti; Novita Tenoyo (Business Accounting Review, 2021)
This study aims to know how investor react to corporate action announcement and which categoriesthat react more positively. Investor’s reaction is measured by cumulative abnormal returns (CAR) with [-2, 0,+2] and [-1, 0, +1] event windows. This study have a total 551 sample data, which are 429 data that do corporateaction and 122 data that don’t do corporate action from automobile manufacturers firms in East Asia in periodof 2017-2020. This study found that investor react more positively to the firms that do corporate action ratherthan firms that don’t do corporate action. Beside that, this study also found that investor react more positivelyto new product category rather than system and technology innovation. This study also found that firm sizenegatively affect investor’s response whereas market capitalization has positive effect to investor’s response.